Proposal of a design method for semi-destructive disassembly with split lines. Issue 1 (2015) - Umeda, Yasushi; Miyaji, Naoya; Shiraishi, Yumi; Fukushige, Shinichi
Abstract This paper proposes a computer-aided design method for semi-destructive disassembly with split lines. This method aims at extracting reusable, recyclable, or hazardous components more efficiently than manual disassembly with higher quality than shredding. The split line is a shape feature of a product that enables to destruct the product into desired shape, like pull tabs of cans. The proposed method aids a designer in adding proper split lines to extract target components. A case study showed that the semi-destructive disassembly sequence of an air conditioner with the split lines reduces the number of steps needed for extracting a target component.